2018
DOI: 10.1111/jdv.15043
|View full text |Cite
|
Sign up to set email alerts
|

Cutibacterium acnes (Propionibacterium acnes) and acne vulgaris: a brief look at the latest updates

Abstract: While the commensal bacterium Propionibacterium acnes (P. acnes) is involved in the maintenance of a healthy skin, it can also act as an opportunistic pathogen in acne vulgaris. The latest findings on P. acnes shed light on the critical role of a tight equilibrium between members of its phylotypes and within the skin microbiota in the development of this skin disease. Indeed, contrary to what was previously thought, proliferation of P. acnes is not the trigger of acne as patients with acne do not harbour more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
362
3
41

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 428 publications
(409 citation statements)
references
References 76 publications
3
362
3
41
Order By: Relevance
“…Although many bacterial species such as C. acnes and S. epidermidis are found as part of the normal flora and are involved in maintaining healthy skin and protection from invading pathogens, the relationship between microorganisms co‐inhabiting the skin is complex and it has been shown that in some cases commensal bacteria can be implicated in certain skin conditions, such as acne . Other research studies have demonstrated that invading bacteria can exacerbate some skin conditions, such as S. pyogenes which is a significant pathogen involved in soft tissue infections and impetigo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many bacterial species such as C. acnes and S. epidermidis are found as part of the normal flora and are involved in maintaining healthy skin and protection from invading pathogens, the relationship between microorganisms co‐inhabiting the skin is complex and it has been shown that in some cases commensal bacteria can be implicated in certain skin conditions, such as acne . Other research studies have demonstrated that invading bacteria can exacerbate some skin conditions, such as S. pyogenes which is a significant pathogen involved in soft tissue infections and impetigo .…”
Section: Discussionmentioning
confidence: 99%
“…A change in the microbial diversity can impair and dysregulate skin defense and thereby increases the chances of damage, infection and inflammation . Although invading pathogens can cause significant damage, in some cases, inflammation is sometimes a result of an immunological response from the host against resident skin commensals, for example some strains of Cutibacterium acnes ( C. acnes, aka Propionibacterium acnes ), are found to be in higher abundance in subjects with acne vulgaris compared to other strains …”
Section: Introductionmentioning
confidence: 99%
“…Initially, the divergent growth rates and robustness of Staphylococcus cultures resulted in a vast overestimation of their presence and role, and the initial difficulty in the cultivation of Cutibacterium hampered efforts to elucidate their role . Despite these complications, C. acnes has long been considered the primary suspect as an acne pathogen . To understand why C. acnes carries a heavy burden of responsibility, one must consider the significant evidence for its potential role.…”
Section: Acne and Skin Bacteriamentioning
confidence: 99%
“…In the first article of this supplement, the authors review the most recent data on C. acnes and its involvement in etiopathogenesis of acne . New findings on C. acnes have revealed that, contrary to what was previously thought, its proliferation is not the trigger of acne.…”
mentioning
confidence: 97%
“…In particular, the presence of C. acnes phylotypes in patients with acne and healthy subjects is discussed: some C. acnes strains and unique genomic sequences seem to be associated with acne development and severity. In the same article, a review of the state of the art on virulence factors, the role and importance of biofilms in resistance of C. acnes to antibiotics and the relationships between phylotypes and antibacterial susceptibility are presented …”
mentioning
confidence: 99%